2003
DOI: 10.1088/0953-8984/16/2/023
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electron beam induced current contrast of deformation-induced defects in silicon

Abstract: Electron beam induced current (EBIC) investigations of plastically deformed silicon in the temperature range from 90 K to 300 K were carried out. It is found that the dislocation trails left behind moving dislocations are the main defects revealed by the EBIC in crystals deformed in clean conditions. With an increase of the contamination level, the dislocation contrast in p-type samples increases. It is observed that the EBIC contrasts of both dislocations and dislocation trails increase with cooling in p-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…The role of such defects could play dislocation trails, i. e. some specific defects formed behind moving dislocations in the dislocation slip planes. Indeed, such defects provide the noticeable EBIC contrast even in Si deformed in clean conditions, when the dislocation contrast is below the detectivity limit [13,14]. These defects could be revealed by chemical etching [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of such defects could play dislocation trails, i. e. some specific defects formed behind moving dislocations in the dislocation slip planes. Indeed, such defects provide the noticeable EBIC contrast even in Si deformed in clean conditions, when the dislocation contrast is below the detectivity limit [13,14]. These defects could be revealed by chemical etching [15].…”
Section: Resultsmentioning
confidence: 99%
“…At low beam energy the contrast inside the depletion region was observed [10,11], which was ascribed to misfit dislocations near strained Si/SiGe interface. However, recent investigations of individual dislo- ¶ E-mail: yakimov@ipmt-hpm.ac.ru cations in clean Si wafers [12][13][14] showed that their EBIC contrast was negligible. In the same time the electrically active defects can be formed behind moving dislocations (dislocation trails), which could produce the rather strong EBIC contrast even in clean crystals [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 5. Such asymmetry in the dislocation electrical activity has been noted before in Electron Beam Induced Current (EBIC) studies [35]. This can be explained on the one hand by the predominant acceptor-like nature of the TD-induced deep levels in the SiGe buffers and by the fact that in n-type material, a barrier builds up around the dislocation line when it becomes progressively filled up with electrons.…”
mentioning
confidence: 60%
“…One of the ideas gaining more and more popularity is that the glide of TDs in relaxed SiGe layers leaves behind a trail of point defects in the glide plane [27,28,35,36], for example by the non-conservative dragging of jogs in the dislocation structure. Positron annihilitation has shown the presence of open volume defects in plastically deformed semiconductors [36], pointing to the presence of vacancy clusters.…”
mentioning
confidence: 99%